Narrative Abilities of Adults’ With Down Syndrome as a Window to Their Morphosyntactic, Socio-Cognitive, and Prosodic Abilities - Martzoukou, Maria; Nousia, Anastasia; Marinis, Theodoros (Frontiers in Psychology, 2020)
Down syndrome (DS) is the most common developmental disorder characterized by mild to moderate intellectual disability. Several studies have reported poor language and prosodic skills and contradictory results regarding individuals’ with DS socio-cognitive skills, whereas most of them have focused on children with DS. The present study attempts to explore adults’ with DS language, socio-cognitive and prosodic abilities via the use of story-retellings. Twenty adults with DS and two groups of TD children, one matched to their expressive vocabulary (TD-EVT) and the other matched to their nonverbal mental age (TD-RCPM), took part in the present study. Participants listened to a story while viewing a wordless picture PowerPoint presentation on a computer screen, and then, they were instructed to retell the story while viewing the pictures for a second time. Each participant listened to two stories, one with “lively” and one with “flat” prosody. Results revealed that adults’ with DS performance was comparable with the one presented by the TD-RCPM group, whereas the TD-EVT group performed significantly better in almost all variables. Individuals’ with DS re-narrations, however, contained significantly less complement clauses and internal state terms (related or not related to Theory of Mind - ToM) compared to the re-narrations of both control groups. In contrast, the group with DS performed similarly to both control groups in comprehension questions related to main characters’ internal state terms and significantly better compared to the TD-RCPM group in questions related to ToM. In terms of prosody, all three groups performed significantly better on story structure and comprehension questions when prosody was “lively” compared “flat” prosody. DS group’s re-narrations did not contain enough internal state terms, not due to their inability in recognizing them, but due to their poor morphosyntactic abilities, which did not allow them to find the proper means to express the main characters’ internal states. Prosody facilitated participants with DS in the comprehension and re-narration. This suggests that intervention programs based on prosody could support the language skills of adults with DS.